Black bear fitness and interactions with humans in an anthropogenic context - Nelson, Shelley Laine, author; Aubry, Lise M., advisor; Aldridge, Cameron L., committee member; Baruch-Mordo, Sharon, committee member; Reynolds-Hogland, Melissa, committee member (Colorado State University. Libraries, 2022)
Multiple studies confirm that anthropogenic pressure has reshaped at least 75% of the global terrestrial biosphere, converting these areas to more anthropogenic biomes. These anthropogenic landscapes have played a key role in altering vertebrate life history strategies (e.g., shifts in breeding phenology, reduced home range, increased competition for resources, increased mortality from anthropogenic causes). Large carnivores are particularly at risk in anthropogenic landscapes because of their large home ranges, high dietary needs, and long generation times, which increases their likelihood of conflict with humans. In the northeastern U.S., populations of American black bears (Ursus americanus) have increased rapidly, more than any other black bear population in the country, with human-bear interactions (HBI) on the rise since the middle of the 20th century. One state in particular, New Jersey, currently sustains the highest coupled density of black bears and humans in the country. Previous research in New Jersey found anthropogenic environments supported higher cub production of female black bears than wildland conspecifics, but females also suffered higher mortality costs. Knowledge gaps remain of the specific ecological components contributing to changes in female black bear (sow) fitness and how these shifts may shape the dynamics of HBI. To bridge these knowledge gaps, I first used statewide, long-term HBI reported incidents (2001 – 2017) in New Jersey, and quantified relative risks and shifts in HBI over space (e.g., land cover types) and time (e.g., bear life cycle stages). I then used 35 years of sow den surveys (1984 – 2019) to examine the relative effects of anthropogenic change (e.g., garbage production, urban development), landscape composition and configuration, natural resource availability, harvest, and individual characteristics (e.g., prior conflict behavior) on sow reproductive components (e.g., body mass and litter size). I found HBI varied by bear life cycle stage and landcover type, and individual characteristics and the environmental context experienced by sows both played important roles in shaping sow fitness and reproduction. I found there were significantly lower odds of more severe HBI during denning. When bears emerge from dens in the spring, there were significantly higher odds of more nuisance HBI, and more specifically garbage complaints. During the breeding and summer activity period, there were significantly higher odds of both benign and more severe HBI occurring. During hyperphagia there were higher odds of more severe and nuisance HBI, when bears are foraging excessively to prepare for winter denning. Spatially, most conflicts occurred in anthropogenic-dominated areas, which also supported the highest odds of garbage complaints. Agricultural areas also supported the highest odds of more severe HBI. My results demonstrated sow body mass is tightly linked to agricultural and developed-low intensity land covers, likely due to the reliable food subsidies in those landscapes, but only apparent within certain sow home range extents. Yet, I found specific anthropogenic food subsides (e.g., trash and corn production) may not be as important to sows, rather increased anthropogenic stimuli (e.g., from cultivated crop and developed-low density land covers) is. I also found that a prior history of conflict with humans contributed to increased sow body mass. Litter size varied with respect to maternal condition, experience, and litter composition (e.g., same sex-female or male litters, mixed sex litters). Results failed to support the assumption of a trade-off between litter size and litter mass that is implicit in many life-history studies. Though, I found litter size and mass were more constrained in older sows compared to younger and middle-aged sows, with a similar relationship apparent in lighter sows versus medium weight and heavy sows. Results revealed sows could be investing more into sons in male-biased triplet litters, because their litter mass exceeded litter mass in other litter types (e.g., female-biased, same sex ratio). My results demonstrate sows may be circumventing trade-offs by continually acquiring more resources for larger litter size and mass, which is likely contributing to the high abundance and success of black bears in New Jersey. My results provide valuable insight in directing management focus towards specific life cycle events and land cover types, where anthropogenic change may simultaneously influence reproductive fitness and HBI, which often results in negative outcomes for black bears in New Jersey. Between 2001 and 2015, >$12 million has been allocated to bear management in New Jersey which at current conflict levels is not economically, environmentally, or socially sustainable long term. My results help guide management so that black bears can continue to thrive in the northeastern U.S., while minimizing human-bear conflicts and cost associated with them, and thus maximizing human-black bear coexistence in this human-dominated landscape.
Keywords: female body mass; litter size; black bear; Ursus americanus; human-bear conflict